ENGLISH LEARNING MODEL AT HOME AND ONLINE APPLICATIONS USED TO INCREASE HEALTH VOCABULARY - Asep Herry Hermawan; Siti Ahadiah Nurjanah; Deni Darmawan (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
Effort to prevent the spread of the COVID-19 corona virus from becoming more massive, the President of Indonesia urged the public activities such as learning, working and doing worship should be carried out at home. Despite giving a statement not to leave the house, President advised the people not to be panic and remain productive even though working from home. Restrictions imposed by governmental agencies had an impact on the daily routine for millions of people, including students in Indonesia. Some schools and universities in certain affected areas had suspended face-to-face learning for a period of time to prevent the spread of COVID-19. What do the students do during the school closed? This study was applied survey method through used online application Learning Model. With internet technology and smart devices, teaching and learning activities can now also be done at home. This study was conducted to increase student’s health vocabularies.